Peran Forum Kerukunan Umat Beragama (FKUB) dalam Menjaga Solidaritas Sosial Antar Pemeluk Agama di Kota Denpasar - Lawalata, Giralda Martje; Suka Arjawa, I Gusti Putu; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI: SOROT, 2022)
This research analyzes and explains the role of the Religious Harmony Forum (FKUB) in maintaining social solidarity among religious believers in Denpasar City. The approach used is qualitative with descriptive types and analysis using Emile Durkheim's theory of social solidarity. The life of urban communities shows some characteristics of social solidarity, especially organic solidarity. Based on the research that has been done, FKUB Denpasar City has played a good role, but not yet maximal because there are still religious conflicts, namely conflicts in the legality of mosque waqf land managers, theological conflicts, musala and church construction permits, and facilities supporting the process of worship. FKUB Denpasar City also faces obstacles, namely lack of supporting facilities, limited management time, and lack of community understanding of the rules and conditions in establishing houses of worship. Keywords: FKUB, Social Solidarity, Religious People of Denpasar City.